Antineoplastic therapy-induced pulmonary toxicity. Issue 8 (August 2013) - Sadowska, Anna M; Specenier, Pol; Germonpre, Paul; Peeters, Marc
Pulmonary complications of antineoplastic therapy are common and are an important cause of respiratory morbidity. The pulmonary toxicity should be taken into account in every patient with respiratory problems who is or has been treated with antineoplastic agents. The diagnosis of drug-induced pulmonary toxicity is complex and should be based on the medical history, clinical, radiological and pathological findings. None of them are specific but they can guide the diagnostic process. The treatment of pulmonary abnormalities caused by chemotherapy is mostly supportive and based on cessation of the causative agent. However, the therapeutic options in oncology setting are usually limited thus the decision about changing the treatment should be taken with caution.